MEASURING THE WEBSITE QUALITY OF ADISUTJIPTO COLLEGE OF TECHNOLOGY BASED ON THREE DIMENSIONS (USABILITY, INFORMATION QUALITY AND SERVICE INTERACTION) - Dwi Nugraheny; Yuliani Indrianingsih; Aldio Bima Saifullah (Compiler, 2020)
Perceptions about the quality of education are the ability to provide an assessment of the superiority of an educational service that can produce academic and non-academic excellence for students by reffering to input, the process of outcomes and the impact it causes. One of the non-academic service on institutions to users, especially students is a website. One of the vision of educational institutions is to provide service to students electronically through website and be expected that the college website can provide the best possible information to students. This study discusses how to measure the website quality of Adisutjipto College of Tehcnology (STTA) using 3 (three) dimensions; Usability, Information Quality and Service Interaction. This research is a descriptive study with a survey method. The research instrument used a questionnaire. The research subjects were 50 STTA students. The results of the measurement survey which are affected by those three dimensions shows that the quality of the STTA’s website is in the “Medium” category.